Rate of convergence on Baskakov-Beta-Bezier operators for bounded variation functions - Vijay Gupta (International Journal of Mathematics and Mathematical Sciences)
We introduce a new sequence of linear positive operators Bn,α(f,x), which is the Bezier variant of the well-known Baskakov Beta operators and estimate the rate of convergence of Bn,α(f,x) for functions of bounded variation. We also propose an open problem for the readers.